The impossible patriotism project - Skeers, Linda (Dial Books for Young Readers, 2007)
Caleb has a hard time coming up with a way to symbolize patriotism for Presidents' Day until he realizes that his dad, who is away from home in the military, is what patriotism is all about. Caleb's class is making projects that represent patriotism to display at Parents' Night. Molly dresses up like the Statue of Liberty and Kareem draws a map of the United States. But Caleb can't think of a single way to show what patriotism means to him. Besides, his dad can't even come to Parents' Night because he is far away, serving as a soldier. Then, when Caleb really starts thinking about his dad and what he is doing for the country, inspiration finally strikes!